Crowding competes with trapping to enhance interfacial diffusion - Cvitković, Mislav; Ghanti, Dipanwita; Raake, Niklas; Smith, Ana Sunčana (European Physical Journal Plus, 2022)
Diffusion of species on biological membranes or materials interfaces is expected to slow down with an increase in their density, but also due to their intermittent binding to functional moieties or surface-defects. These processes, known as crowding and trapping, respectively, occur simultaneously in a broad range of interfacial systems. However their combined effect on the diffusion coefficients was not studied hitherto. Here, we analytically calculate and numerically validate by Monte Carlo simulations an expression for the diffusion coefficient of a two-dimensional lattice gas in a field of immobilized traps. As expected, trapping and crowding both suppress transport but, surprisingly, the diffusion coefficient is non-monotonous. Namely, increasing gas densities increases trap occupancy while crowding is not overpowering, such that the diffusion reaches a maximum. These results should be relevant to interfacial growth phenomena, as discussed in the context of nascent adhesions in cells.
CRIS-Team Scopus Importer:2022-03-25